The Myth of the Decline Effect in Psi Research: The Empirical Evidence - Tressoldi, Patrizio E; Storm, Lance (Journal of Scientific Exploration, 2024)
The decline effect (DE) has been discussed in “psi” research since the early times of experimental investigations, and many causes have been advanced from: individual psychology, social attitudes, electromagnetic fields, experimental artifacts, or physical properties often related to quantum physics. Bierman (2001) found small and statistically significant decline slopes in all experimental protocols, but the mind-matter interaction with random number generators, where he found a positive quadratic polynomial slope. This study aimed to update Bierman’s results, taking into account all studies completed up to 2023 and analyzed in different meta-analyses. Five experimental protocols were analyzed: including anomalous perception in a Ganzfeld condition, remote viewing, forced-choice design in extra-sensory perception, predictive physiological anticipation, and dream extra-sensory perception studies. The results showed that only one slope coefficient out of the five examined was statistically significant, indicating that there was no evidence of a general DE across the different experimental protocols.